(3GdJGQjN GdcHjQs - (3eMeO Hf ESeGYjd Hf EHQGgje Hf GdeZjQI GdHNGQj, CHh YHO Gddg,J (B256 (3g` s
(3ChdgG (B:s
(3ZjQ ehLhO HGdagQS s
(3GdehLhO (B: (3bWYI efg JHOC HJQLeI eMeO Hf YHO GdhGMO Hf CHj MRe GdbWYi GdHUQis
(3GfXQ GdbSe GdChd Qbe (B123s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B52s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B159 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B264 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B79 s
Keywords: (3GdJGQjNs